PENGARUH LIFESTYLE DAN LABEL HALAL TERHADAP KEPUTUSAN PEMBELIAN PRODUK WARDAH DESA WONOSARI KECAMATAN TANJUNG MORAWA KABUPATEN DELI SERDANG - Eka Hitmawati; Falahi, Adrial; Hidayat, Toni (Program Studi Manajemen Fakultas Ekonomi dan Bisnis, Universitas Muslim Nusantara Al-Washliyah, 2023)
This research aims to determine the influence of lifestyle and halal labels on purchasing decisions for Wardah products in Wonosari Village, Tanjung Morawa District, Deli Serdang Regency. The population is the people of Wonosari Village, Tanjung Morawa District, Deli Serdang Regency, totaling 76 people. Determination of the sample using accidental sampling. The data analysis technique in research is quantitative descriptive. Data collection was done by giving questionnaires to respondents. This research uses data analysis techniques, namely multiple linear regression analysis, t test, F test, and coefficient of determination. The results of multiple linear regression analysis obtained Y = 2.062+0.539X1+0.420X2, the results of the t test (partial) show that lifestyle (X1) has a significant effect on purchasing decisions, this can be seen from tcount 6.113> ttable 1.993 with a significance of 0.000 <0.05 . The halal label variable (X2) has a significant effect on purchasing decisions, this can be seen from tcount 5.332 > ttable 1.993 with a significance of 0.005 <0.05. The results of the F test (simultaneous) obtained an Fcount value of 106.714 > Ftable 3.12 with a significance of 0.000 < 0.05. This shows that together the lifestyle variables and the halal label have a significant influence on purchasing decisions for Wardah products, Wonosari Village, Tanjung Morawa District, Deli Serdang Regency. The R Square (R2) value is 0.745. This means that the influence of lifestyle and halal labels on purchasing decisions is 74.5%.